2014
DOI: 10.1016/j.aip.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Art psychotherapy practice with adults who suffer from depression in the UK: Qualitative findings from a depression-specific questionnaire

Abstract: Please cite this article as: Zubala, A., MacIntyre, D. J., and Karkou, V.,Art psychotherapy practice with adults suffering from depression in the UK: qualitative findings from depression-specific questionnaire., The Arts in Psychotherapy (2014), http://dx.doi.org/10. 1016/j.aip.2014.10.007 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
3
5
0
1
Order By: Relevance
“…This agrees with findings in other studies (Blomdahl et al, 2013;Gunnarsson, Peterson, Leufstadius, Jansson, & Eklund, 2010;Zubala, MacIntyre, & Karkou, 2014). The study reported by Zubala et al (2014) described therapeutic aims for treating depressed patients and identified four art-related tools useful in helping patients express their problems and emotions and explore the meaning of their depression. In this study there were contradictory results concerning communication.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with findings in other studies (Blomdahl et al, 2013;Gunnarsson, Peterson, Leufstadius, Jansson, & Eklund, 2010;Zubala, MacIntyre, & Karkou, 2014). The study reported by Zubala et al (2014) described therapeutic aims for treating depressed patients and identified four art-related tools useful in helping patients express their problems and emotions and explore the meaning of their depression. In this study there were contradictory results concerning communication.…”
Section: Discussionsupporting
confidence: 90%
“…Despite their different frames of reference, they agreed on what is therapeutic. This results agrees with findings ofZubala et al (2014) of an eclectic use of different theories. The experts seem to feel supported by several different theories, perhaps depending on the situation.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It is thus important that the therapists understand the concepts core to depression and likely to play a vital role in the therapy process, e.g. time, layers of symptoms covering the main problem, the feeling of being trapped, the need for hope and relaxation to relieve initial tension (Zubala et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…This paper describes the work of an NHS based clinician researcher group (CRG) working with community out-patients with a diagnosis of complex depression where there was currently a gap in evidence-based approaches and where art psychotherapy was perceived to offer accessible and effective treatment. The predominant model of art psychotherapy for CD identified in the overview of the literature, has been driven by an understanding of relational dynamics, such as processing transference and countertransference phenomena and how these dynamics are intrinsic to dynamic representations produced in the artworks in art psychotherapy (Barbee, 1996 ; Zubala et al, 2014 ; Blomdahl, 2017 ; Zubala and Karkou, 2018 ). The secondary aim was to investigate where shared practice based principles were salient to a dynamic change process, including and in particular automatic and improvised expression (Keeney, 1991 ; Lobb, 2003 ; Blomdahl et al, 2013 ; Haslam et al, 2019 ), interpersonal articulation that allows naming and reflecting on complex emotional experiences (Gruber and Oepen, 2018 ; Zubala and Karkou, 2018 ) and developing narratives within a safe therapeutic relationship (Carlson, 1997 ; Bochner and Ellis, 2003 ; Gruber and Oepen, 2018 ).…”
Section: The Aim Of This Studymentioning
confidence: 99%